2018
DOI: 10.2147/ott.s157707
|View full text |Cite
|
Sign up to set email alerts
|

Chelerythrine induced cell death through ROS-dependent ER stress in human prostate cancer cells

Abstract: IntroductionProstate cancer is the most common noncutaneous cancer and the second leading cause of cancer-related mortality worldwide and the third in USA in 2017. Chelerythrine (CHE), a naturalbenzo[c]phenanthridine alkaloid, formerly identified as a protein kinase C inhibitor, has also shown anticancer effect through a number of mechanisms. Herein, effect and mechanism of the CHE-induced apoptosis via reactive oxygen species (ROS)-mediated endoplasmic reticulum (ER) stress in prostate cancer cells were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…PCa is known as the most frequent non-cutaneous cancer and the second main cause of cancer-related mortality in all the countries [ 21 ]. The challenges for the treating the patients with PCa are because of the shortage of understanding the molecule mechanism of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…PCa is known as the most frequent non-cutaneous cancer and the second main cause of cancer-related mortality in all the countries [ 21 ]. The challenges for the treating the patients with PCa are because of the shortage of understanding the molecule mechanism of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proved that CHE causes prostate cancer cell apoptosis mainly related to the activation of ER stress signalling pathway. 16 Besides, it has been report that oxidative stress modulating drugs activate the ER stress-related apoptosis. 18 Thus, we speculated that ER stress contributed to renal cancer cells apoptosis by CHE treatment.…”
Section: Che Caused Ros-dependent Er Stress Activation In Human Renmentioning
confidence: 99%
“…In the case of chelerythrine chloride treatment, there could be involvement of ROS generation beyond what the intrinsic cellular antioxidants could handle, thus leading to oxidative stress and cell death. Indeed, several studies including in NSCLC, prostate cancer and renal cell carcinoma confirmed that chelerythrine-induced cell death was mediated through ROS generation and was reversible upon pre-treatment of the ROS scavenging agent-N-acetyl-l-cysteine (NAC) [22,23,50]. Different type of cell death can ensue depending on the amount of ROS generated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies over the years have successfully established the apoptotic-inducing ability of chelerythrine in a variety of cancer cells, namely in uveal melanoma, leukemia, prostate cancer, hepatoma, and renal cancer [17][18][19][20][21]. The latest reports suggest apoptosis is mediated through reactive oxygen species (ROS)-dependent endoplasmic reticulum (ER) stress induction and possibly through signal transducer and activator of transcription 3 (STAT3) inactivation [22,23]. Studies also showed that chelerythrine was able to inhibit the growth of cisplatin-resistant NSCLC and triple-negative breast cancer cells as well as sensitizing them to chemotherapies [24,25].…”
Section: Introductionmentioning
confidence: 99%